UPAYA PENGEMBANGAN WISATA MELALUI PEMBUATAN PAPAN PETUNJUK ARAH DAN PETA SEBAGAI FASILITAS PENUNJANG DESTINASI WISATA DESA LABUHAN HAJI - Syamsuhaidi, Syamsuhaidi; Jayadi, Misrul Efendi; Astuti, Ni Luh Vinna Puja; Setyaningtyas, Siti Cahya Hemas; Massayres, Devina Ayu; Julianti, Elsa; Safari, M; Alfarisi, Muhammad Farrel; Usmiatun, Ita; Sunarto, Wiji Widiansari; Hidayatullah, Muhammad Razhu (Universitas Mataram, 2023)
Labuhan Haji Village has a potential tourist destination. Labuhan Haji Beach has a tourist attraction because around Labuhan Haji beach it not only provides beautiful views but there are mostly grilled fish sellers, food stalls and cafes managed by investors. The problem with the Labuhan Haji beach tourism destination is that they don't have access to markers or directions to tourist sites in Labuhan Haji, especially for new visitors to the area. Directional signs and bulletin boards are very important to show directions and locations in a tourist destination area, as a guide to tourist locations. The absence of direction signs and bulletin boards makes it difficult to find tourist destinations in the village of Labuhan Haji. This Village Community Empowerment Real Work Lecture activity aims to design, manufacture, and install signboards and bulletin boards. The construction of direction boards and bulletin boards consists of poles, plate boards, writing and banners. The pole is designed to be made of iron as high as 2.5 meters. Directional signs are designed to be 60 cm long, 12 cm wide and 0.8 mm thick, made of iron plate. Writing is designed with computer software and made by cutting method and then given a white pilox. While the bulletin board is designed to be made of iron as high as 3 meters and the plate board is designed to be 100 cm long, 70 cm wide and 0.8 mm thick. Iron pole and plate board are welded into one piece with arrow shape. Work on direction signs and bulletin boards includes cutting, welding, sanding, painting, pasting writing, spraying pilox, removing writing residue, excavation and installation.